A 40nm CMOS operational amplifier for internet-of-things applications - Cheng, Yujie (2017)
Operational amplifier is an important part for the analog and mixed signal circuit. It is widely used in buffers, summers, comparators, so forth. Operational amplifier is also well studied with multi-stages and different compensation techniques. One of the compensation technique is the versatile three stage operational amplifier with second stage bypass compensation dedicated to Internet-of-Thing application. That compensation technique can provide large bandwidth and it can drive large capacitive load. The reported amplifier serves as a benchmark, and this work will modify from the benchmark to present a new structure which is more suitable for low power application for IoT application. The performance comparison of the proposed work and the benchmark has been conducted under different loading conditions. It turns out that the proposed work is more suitable for IoT application in view of wider bandwidth and better slew rate and settling time under low power condition. This work is simulated using TSMC 40nm technology with Candence VIRSUOTO software.